Short‐time effect of intravitreal injections on retinal vascular oxygenation and vessel diameter in patients with diabetic macular oedema or neovascular age‐related macular degeneration. Issue 3 (25th October 2019) - Mitsch, Christoph; Pemp, Berthold; Pollreisz, Andreas; Gleiss, Andreas; Karst, Sonja; Scholda, Christoph; Sacu, Stefan; Schmidt‐Erfurth, Ursula
Abstract: Purpose: To investigate the short‐time effect of intravitreal injections (IVI) of the vascular endothelial growth factor inhibitors ranibizumab and aflibercept on retinal arterial and venous oxygen saturation (SO2a and SO2v), arteriovenous oxygen saturation difference (AVD) and vessel diameter (VDa and VDv) in patients with diabetic macular oedema (DME) and patients with choroidal neovascularization (CNV) due to age‐related macular degeneration. Methods: Uncontrolled prospective observational study in 100 eyes. Retinal vessel oxygen saturation and diameters were assessed using a retinal oximeter before and minutes after IVI of ranibizumab or aflibercept. Results: 40 eyes with CNV and 34 eyes with DME were included in the analysis. At baseline, SO2a and SO2v were significantly higher in DME (p = 0.043 and p = 0.009, respectively). After IVI, SO2a significantly decreased in CNV and DME eyes by 2.6% (p = 0.016) and 4.6% (p = 0.002) and SO2v decreased by 14.0% (p = 0.004) and 12.4% (p = 0.017), respectively. However, a significant increase in AVD was only found in CNV (15.7%, p = 0.001). VDa decreased significantly only in DME by 5.7% (p = 0.010). No medication‐specific disease effect was found and vice versa. Conclusions: The observed changes can be interpreted as signs of increased metabolic demand during the physiological stress after an IVI. The abnormal arterial constriction and the abolished increase in AVD seen only in eyes with DME indicate an impairment of vascular autoregulation and oxygen distribution and a reduced neuroretinal metabolism in the diabetic retina with a significant impact on inner retinal oxygen consumption shortly after IVI.